Hydrological Monitoring as A Tool to Evaluate Soil and Water Conservation Activities - Honore, G. (Journal of Soil and Water Conservation, 2022)
This paper argues that there is a need to improve monitoring and evaluation of soil and water conservation schemes. Hydrology monitoring can be a solution if used and applied scientifically. The paper then presents experiences of the Indo-German Bilateral Project 'Watershed Management' with regard to hydrological monitoring as a tool to evaluate soil and water conservation programs.